2014
DOI: 10.1016/j.bbadis.2014.04.031
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between MMP-9 and extracellular cytokine HMGB1 in prediction of human ischemic stroke outcome

Abstract: Ischemic stroke (IS) outcome predictors include clinical features, biochemical parameters and some risk factors. The relations between two main players in the ischemic brain, MMPs and HMGB1, were estimated in the plasma of ischemic stroke patients stratified according to the Glasgow Outcome Scale and the Oxfordshire Community Stroke Project classification. IS patients exhibited higher plasma concentration of MMP-9 and the inflammatory cytokine HMGB1 compared with healthy controls. A full-blown correlation betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 26 publications
2
37
0
Order By: Relevance
“…MMPs, one kind of matrix-degrading enzymes, including MMP-9, cause cerebral neuroinflammation [33,34]. In the present study, we found that thrombin induced MMP-9 expression associated with cell migration of SK-N-SH cells.…”
Section: Discussionsupporting
confidence: 56%
“…MMPs, one kind of matrix-degrading enzymes, including MMP-9, cause cerebral neuroinflammation [33,34]. In the present study, we found that thrombin induced MMP-9 expression associated with cell migration of SK-N-SH cells.…”
Section: Discussionsupporting
confidence: 56%
“…Previous studies show that HMGB1 increases in patients with ischemic stroke and correlates with the number of circulating leukocytes, 27 stroke severity (NIHSS score, infarct size), and inflammatory markers (TNF-a, IL-1, IL-6, MMP9). [28][29][30][31] These findings are consistent with our study whereby a decrease in let7i was associated with a rise in HMGB1 as well as an increase in inflammatory response, MMP9, and infarct size.…”
Section: Neurology 87 November 22 2016supporting
confidence: 91%
“…In the early phase subsequent to cerebral ischemia, MMPs disrupt the BBB, leading to BBB leakage, leukocyte infiltration, brain edema and hemorrhage (41). Within the MMP family, MMP-2 and MMP-9 have been regarded as the key enzymes associated with secondary damage following ischemic cerebral stroke (42).…”
Section: Discussionmentioning
confidence: 99%
“…Within the MMP family, MMP-2 and MMP-9 have been regarded as the key enzymes associated with secondary damage following ischemic cerebral stroke (42). Clinical data support that the activated MMP-9 can be considered as an effective marker for negative outcome within the early phase of ischemic stroke development (41). Therefore, MMP-9 is a potential therapeutic target for BBB disruption following thrombolysis (43).…”
Section: Discussionmentioning
confidence: 99%